2011
DOI: 10.1155/2011/941895
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine (ADMA) Levels Display a Morning Peak in Patients with Acute Myocardial Infarction

Abstract: Abstract. High Asymmetric Dimethylarginine (ADMA) levels are associated with increased platelet activity, elevated blood pressure, vasoconstriction and impaired vascular relaxation. We hypothesized that the myocardial infarction morning peak of occurrence is closely related to a morning peak of ADMA levels. We performed a cross-sectional study among patients with documented myocardial infarction who had been enrolled in the prospective MISSION! Intervention Study. In total, serum ADMA levels were measured in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(56 reference statements)
0
10
0
1
Order By: Relevance
“…To our knowledge, there have been no reports about circadian variation of GABR. Only one paper suggested that serum ADMA concentration has diurnal variation with a morning peak 36) , which is the opposite pattern to that of endothelial function. In the present study, time of day of blood sampling varied depending on the schedule of coronary angiography, which could obscure the differences in GABR and ADMA values between patients with or without CAD because of diurnal variation.…”
Section: Study Limitations and Clinical Implicationsmentioning
confidence: 99%
“…To our knowledge, there have been no reports about circadian variation of GABR. Only one paper suggested that serum ADMA concentration has diurnal variation with a morning peak 36) , which is the opposite pattern to that of endothelial function. In the present study, time of day of blood sampling varied depending on the schedule of coronary angiography, which could obscure the differences in GABR and ADMA values between patients with or without CAD because of diurnal variation.…”
Section: Study Limitations and Clinical Implicationsmentioning
confidence: 99%
“…A total number of 20 out of 25 relevant articles investigated the circadian rhythms impact on coagulation, fibrinolysis, or both in healthy persons only or together with cardiovascular patients [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The remaining articles addressed the same question in cardiovascular patients only and represent four different study designs; two longitudinal observational studies [32,33], One comparative retrospective study [34] and One cross-sectional study [35].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found a circadian rhythm of Lp(a) or ADMA [34,35]. Both studies only included AMI patients, but represent two different study designs.…”
Section: Lipoprotein a (Lp(a)) And Asymmetric Dimethylarginine (Adma)mentioning
confidence: 99%
See 1 more Smart Citation
“…данным ряда исследований, TFN является косвенным маркером ЭД[6; 7].Асимметричный диметиларгинин (ADMA) является эндогенным ингибитором синтазы оксида азота (NO), маркером ЭД. Повышение его уровня связано с риском острых коронарных событий, нарушениями перфузии миокарда и неблагоприятным прогнозом у пациентов с ИМ[8].Еще одним перспективным биомаркером воспаления и ЭД является цитокинфракталкин/CX3CL1[9]. В доступной литературе представлены единичные исследования по изучению его уровня у пациентов с ИМ.…”
unclassified